HomeBud: A Smart IoT Watering System for Indoor Plants - Liang, Billie; Chen, Victoria; Tian, Kasey; Bigos, Izabela; Jokic, Kristina; Haghani, Sasan (Proceedings of IEEE International Symposium on Consumer Electronics, 2025)
Indoor plants are known to benefit their owners in a variety of ways. Plants can serve useful functions within the home, such as herbs for cooking or various plants for insect repelling, or increase one's mental health by lowering stress levels. Unfortunately, caring for plants can be difficult for people who have busy schedules, lack experience in plant care, or have health complications or disabilities. This paper explores a way to automate plant care-taking while being space, time, and cost-efficient. The system runs on an Arduino Uno R4 which automates the plant watering process and uses a grow light in order to ensure that the plant is getting the appropriate amount of light every day. This system can be controlled using an app, which allows for monitoring as well as setting target soil moisture and daily light amounts, which can be tailored for the plant being cared for. Novice users may not know exactly how much water or light their plants may need, so the companion app also include presets for common plants. This system will enable more people to take better care of plants, allowing more people to reap the benefits of keeping indoor plants, even if their lifestyle makes it otherwise difficult.